Disease tolerance and infection pathogenesis age-related tradeoffs in mice - Karina K. Sanchez; Justin L. McCarville; Sarah J. Stengel; Jessica M. Snyder; April E. Williams; Janelle S. Ayres (Nature, 2026)
Abstract Disease tolerance is a defence strategy essential for survival of infections, limiting physiological damage without killing the pathogen 1,2 . The disease course and pathology an infection may cause can change over the lifespan of a host due to the structural and functional physiological changes that accumulate with age. Because successful disease tolerance responses require the host to engage mechanisms that are compatible with the disease course and pathology caused by an infection, we predicted that this defence strategy would change with age. Animals infected with a 50% lethal dose  (LD 50 ) of a pathogen often show distinct health and sickness trajectories due to differences in disease tolerance 1,3 and can be used to define tolerance mechanisms. Here, using a polymicrobial sepsis model, we found that, despite having the same LD 50 , aged and young susceptible mice showed distinct disease courses. In young survivors, cardiac Foxo1 and its downstream effector Trim63 (MuRF1) protected from sepsis-induced cardiac remodelling, multi-organ injury and mortality. Conversely, in aged hosts, Foxo1 and Trim63 acted as drivers of sepsis pathogenesis and death. Our findings have implications for the tailoring of therapy to the age of an infected individual and indicate that disease tolerance genes show antagonistic pleiotropy.